Underlying Processes of an Inverted Personalization Effect in Multimedia Learning – An Eye-Tracking Study - Zander, Steffi; Wetzel, Stefanie; Kühl, Tim; Bertel, Sven (Frontiers in Psychology, 2017)
One of the frequently examined design principles in multimedia learning is the personalization principle. Based on empirical evidence this principle states that using personalised messages in multimedia learning is more beneficial than using formal language (e.g. using ‘you’ instead of ‘the’). Although there is evidence that these slight changes in regard to the language style affect learning, motivation and the perceived cognitive load, it remains unclear, (1) whether the positive effects of personalised language can be transferred to all kinds of content of learning materials (e.g. specific potentially aversive health issues) and (2) which are the underlying processes (e.g. attention allocation) of the personalization effect. German university students (N= 37) learned symptoms and causes of cerebral haemorrhages either with a formal or a personalised version of the learning material. Analysis revealed comparable results to the few existing previous studies, indicating an inverted personalization effect for potentially aversive learning material. This effect was specifically revealed in regard to decreased average fixation duration and the number of fixations exclusively on the images in the personalised compared to the formal version. This result can be seen as indicators for an inverted effect of personalization on the level of visual attention.